If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -3 = -51 Reorder the terms: -3 + 8x = -51 Solving -3 + 8x = -51 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 8x = -51 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = -51 + 3 8x = -51 + 3 Combine like terms: -51 + 3 = -48 8x = -48 Divide each side by '8'. x = -6 Simplifying x = -6
| 6y^2-10y=0 | | 2x^2-13x-45=0 | | n-7=14 | | n+34=54 | | n-13=18 | | 75-5x=31x+15 | | 6+11x=106+6 | | n-9=13 | | -1=-3r+2rp | | 4x+30=12x-58 | | n+36=52 | | n+18=24 | | 9x+7=5x+31 | | 14m=-3-8m^2 | | 4x+34=14x-56 | | 7x-16=47 | | 8x+2=58 | | -32-7x=9x+16 | | 7(h+3)+4=-2 | | -42rst+66r^2s-12rs^2t= | | 2x+10=-23-9x | | (Y+2)(y^2-3y-10)=0 | | 4x+19=8x-9 | | 113-4x=3x+15 | | 138-7x=29x+18 | | 3x+34=5x | | (X^2+5x+4)(6x^2-x-2)=0 | | -9-5x=11-9x | | 8-8x=160-36x | | 5x+34=3x | | 40x^5-5x^4= | | 97-4x=9x+19 |